DESIGN AND DEVELOPMENT OF A WEBSITE AND MOBILE BASED ANIMAL CLINIC INFORMATION SYSTEM (CASE STUDY OF GALAXY SATWA ANIMAL CLINIC): RANCANG BANGUN SISTEM INFORMASI KLINIK HEWAN BERBASIS WEBSITE DAN MOBILE ( STUDI KASUS KLINIK HEWAN GALAXY SATWA ) - Fitri, Devi Yanti Cantika; Sisephaputra, Bonda (Journal of Emerging Information Systems and Business Intelligence (JEISBI), 2024)
All animals definitely need a check-up every month or every year and have experienced an illness that makes pet owners definitely take their pets to the veterinary clinic to keep their animals healthy. One of them is the Galaxy Satwa veterinary clinic. Currently, the recording system at the Galaxy Satwa clinic still uses manual recording and there is no organized appointment system, so doctors often experience many problems and are overwhelmed due to these limitations, such as running out of paper for recording medical records, medical record data being lost or wet, and patient queues piling up. Therefore, the author created an information system that can simplify the operation of the system in clinics which include website and mobile-based medical record recording and appointment arrangements. The research was prepared using the Extreme Programming method. Website system development uses the PHP programming language with the Laravel framework, while for mobile system development uses the Dart programming language with the Flutter framework. The database used in this application is MySQL. For testing, use the Whitebox testing method with the Basic Path technique and the results show that all test cases / paths for the features being tested were successfully run at least once. The Cyclomatic Complexity and independent path values ??for each feature tested are the same, so the system built is appropriate.